(untitled) (Bangladesh Journal of Medical Science, 2022)
Background - Hassall’s corpuscles (HC) are balls of flattened medullary epithelial cells which are characteristic features of the thymus. Thymus is truly an ‘organ of mystery’ which has kept scholars in dark still continues to elucidate researchers till date. Aim- To study themicroscopic features of human fetal thymus along withthe differentiation and maturation process of the Hassall’s Corpuscles (HC) in human fetal thymus by using the immunohistochemical markers. Materials & Methods- Total 20 aborted and still born fetuses ranging from 17-39 weeks of gestation were used for the study. After embalming, meticulous dissection, thymusgland was weighed and fixed with formalin. The various histological and histometric parameters were observed. Another set of microscopic slides were subjected to immunohistochemical studies by staining with primary antibodies (Cytokeratin, S100 and Vimentin) to study the presence of epithelial, histiocytic and mesenchymal components in fetal thymus and to know the nature of differentiation of the Hassall’s corpuscles, epithelial reticular cells and dendritic cells in the fetal thymus. Observations & Results: Microscopic examination of serial section of thymus revealed few patterns of shapes of HC’s. Based on the morphological features, the corpuscles were classified as Solid Hassal Corpuscles (SHC), Cystic I (CHCI) and Cystic II(CHC II) and Degenerating(DHC). Epithelial cells of the HC were positive for cytokeratin which was less intensely positive in Solid Hassall Corpuscles (SHC) and intensely positive in primary and secondary cystic Hassall Corpuscles (CHC I and CHC II). The solid corpuscles (SHC) with homogenous mass were seen to be intensely positive whereas the central core in cystic varieties (CHC 1 & CHC II) seems to be less positive with S 100 (marker for dendritic cells, histocytes and keratinocytes). Vimentin is intermediate cytoplasmic proteins expressed in the cells of mesenchymal differentiation found negative in the complete sections studied. Conclusion:The various types of HC encountered with different structural morphology could represent a stage of maturation in the developmental process. Hence HCs’ were arranged in a sequential order of development stages within the age group of the present study. The presence of Solid Hassall’s Corpuscle at the periphery of the medulla and Degenerating Hassall’s Corpuscle(DHC) at the central core of the medulla confirms the direction of maturation is from the periphery to the center of the medulla. Hence there is gradual increase in the expression of cytokeratin from solid to cystic Hassall’s corpuscles. Bangladesh Journal of Medical Science Vol. 21 No. 03 July’22 Page: 529-539